REVOLUSI ABOLISIONISME PADA NOVEL PERBUDAKAN UNCLE TOM’S CABIN KARYA HARRIET BEECHER STOWE - Amiruddin, Andi (Universitas Andalas, 2019)
Literature and revolution cannot be separated from one another. On one hand, therevolution can create literary works from writers who are responsive to the changes that took placein their time. On the other hand, literary works can trigger the revolution in the people who readthe work. In In Uncle Tom's Cabin, the relationship between literature and revolution can be seenin how the movement of the abolitionism group inspired Harriet Beecher Stowe to fight slaverythrough literary works. Harriet Beecher Stowe described slavery in South America and theabolitionist revolution against abolition of slavery.